Diminishing returns of task-oriented interaction in digitally-mediated dynamic teams: evidence from amateur sports organizing - Jing Yang; Tang Yao; Jun Wang (Frontiers in Psychology)
Although extant research has emphasized task-oriented processes in teams, its focus on dynamic teams in digital environments remains limited, particularly regarding non-linear effects. Integrating attention capacity theory and activation theory, this study proposes a curvilinear (inverted-U) relationship between task-oriented interaction and team organizing efficiency in digitally-mediated teams. Analyzing 455 spontaneous sports teams from an open-boundary organizational platform revealed support for the proposed curvilinear relationship, with team identification moderating the effect. Specifically, when team identification was low (vs. high), the inverted-U relationship was more salient. With high (vs. low) team identification, teams exhibited relatively higher levels of team organizing efficiency, regardless of task-oriented interaction. These findings establish diminishing returns of task-oriented interaction as a fundamental boundary condition for digitally-mediated organizing efficacy, advancing theory on dynamic team coordination and offering pragmatic guidelines for managing technology-mediated sports collaboration.